Development of Pop-Up Book Media on Preventing The Initiation Of Smoking Behaviour Among Primary School Students in Samarinda City - Nino Adib Chifdillah; Eka Putri Rahayu; Dian Ardyanti (Preventif : Jurnal Kesehatan Masyarakat, 2026)
One of the main problems related to smoking is the increasingly young age at which people start smoking and the increasing prevalence of novice smokers. Preliminary results of this study show that students at SDN 002 Loa Janan Ilir still have low knowledge about cigarettes. Preliminary observations also indicate that there is no health education media on smoking prevention in the school area. This study aims to analyze the effect of pop-up books on the behavioral domain of smoking initiation prevention among primary school students in Samarinda. This study was a research and development (R&D) study. The development approach was applied to the development of educational monopoly media. The development of this media used the waterfall development model. A qualitative approach was applied at the research and information collecting stage until the main product revision stage. The type of quantitative research used was a pre-experiment with a one group pretest-posttest design. The results showed that there was an effect of the intervention with pop-up book media on the respondents' knowledge about the dangers of smoking. Statistical analysis using the Wilcoxon test produced a p-value of 0.000 (<0.05). Educational and health institutions are expected to collaborate in the development of health promotion media in the form of pop-up books as an innovative effort to prevent the initiation of smoking behavior among children.